Benefits of Alternative Oil Sources for IV Lipid Emulsions - Rizzo, Toni (MD Conference Express, 2015)
Soybean oil lipid emulsions for parenteral nutrition have been used since the 1960s. Alternative oils were developed to reduce the phytosterols and linoleic acid in soybean oil emulsions, which promote the stress response, suppress immune function, and impair liver function. Clinical studies have demonstrated that olive and other oil sources are safe and effective in adult and pediatric patient populations.